2006
DOI: 10.1016/j.scitotenv.2004.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Role of organic matter in framboidal pyrite oxidation

Abstract: An experimental system has been set up to investigate the reaction kinetics of framboidal pyrite oxidation in real, reactive acid sulfate soil assemblages. This study was undertaken to determine the degree to which pyrite oxidation rates are reduced by bacteriological reactions and organic matter, which both modify the net reaction mechanisms and compete for available oxygen. The results from these experimental runs not only confirm the role of organic matter in mitigating pyrite oxidation but indicate that at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…In this study, the limited oxygen concentration in the influent and the long-term flooding operation created low redox conditions in the microcosms (-200 ~ 50 mV), which may have decreased the pyrite oxidation rates (Johnston et al, 2014). Furthermore, the organic carbon released by the litter could also compete with the reduced S for oxygen, thereby slowing pyrite oxidation (Rigby et al, 2006). In addition to pyrite, some metastable iron sulfides (e.g.…”
Section: Sulfate Transformation In Cwsmentioning
confidence: 89%
“…In this study, the limited oxygen concentration in the influent and the long-term flooding operation created low redox conditions in the microcosms (-200 ~ 50 mV), which may have decreased the pyrite oxidation rates (Johnston et al, 2014). Furthermore, the organic carbon released by the litter could also compete with the reduced S for oxygen, thereby slowing pyrite oxidation (Rigby et al, 2006). In addition to pyrite, some metastable iron sulfides (e.g.…”
Section: Sulfate Transformation In Cwsmentioning
confidence: 89%
“…Different origins have been inferred for framboidal pyrite crystals, including a purely inorganic origin, based on laboratory synthesis and occurrences in magmatic rocks, framboid formation through indirect biogenic processes, and a direct biogenic process of framboid formation [23,34,28,35,36,37]. Occurrence of the studied framboidal pyrite crystals in close association with biodegraded oils in the pores of the oil sands suggests that they were formed as part of the biodegradation processes that occurred in the oil sands.…”
Section: Discussionmentioning
confidence: 98%
“…Our results suggested that techniques based on short‐term sulphide oxidation are not effective and likely to be unreliable in soils containing large percentages of organic matter. The slower rate of pH decrease and the final values obtained in the surface samples suggest retardation in the rate and amount of acid generation by pyrite oxidation because of the concurrent oxygen consumption by organic matter and bacterial activity (Rigby et al. , 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Diverse field techniques and evidence have been traditionally applied acidsulphate soil identification (Dent & Dawson, 1998;Dear et al, 2002;Ahern et al, 2004) and it has become apparent that the characteristics of these soils are area dependent the, results obtained in soils of one area cannot necessarily be extrapolated to similar soils elsewhere, and that none of the simple identification techniques should be employed alone (Thomas & Varley, 1982;Andriesse, 1993). More recently, Rigby et al (2006) criticized the lack of actual rates for 'in situ' pyrite oxidation and hence acid generation rates, to support the construction of worst-case scenarios of the environmental risk of acid-sulphate soils.…”
Section: Introductionmentioning
confidence: 99%